A Socio-Pragmatic Analysis of Social Media Comments on Online Learning at the Time of COVID 19 - Atyaf Hasan; Fatima Abdul Ghany Idrees (Hasanuddin University, 2020)
The fundamental aim of the present study is to analyze the pragmatic aspects of the English social media comments on posts related to online learning at the time of Covid19. The aim in this socio-pragmatic study is to identify the maxims and strategies used by English commenters and the extent to which the commenters follow or flout these and strategies when commenting on posts related to online learning at time of COVID 19. It also aims at investigating how the social media, as a new marvelous vital trend, contributes to increase language and linguistic variation in people's online comments. To achieve these the researchers analyze 25 Facebook comments based on two adopted models; Grice's (1975) maxims and Crystal's strategies (2001) to build a comprehensive picture about the role of age, gender, social status on the comments. The results of the analysis show that both models are applicable and sometimes flouted. Some commenters flout more than two maxims in the same comment and the same is true regarding Crystal's model. It has been found that comments are highly constrained by social factor, while age and gender do not have great significant effect.